Breakthrough in Transformingn Animal Waste into Eco-Friendly Organic Fertilizer: A Sustainable Solution - Riyanto, Sherly Nouvita; Herlian, Elva Margareta; Sumaji, Sumaji (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
The escalating environmental concerns and the demand for sustainable agricultural practices have prompted various initiatives to transform animal waste into eco-friendly organic fertilizers. This research focuses on the conversion of cow and goat manure into Eco Grow fertilizer, a sustainable alternative to chemical fertilizers. This study was conducted in Desa Mrican, specifically Dusun Trenceng, involving 50 participants from local farming groups. The primary objective was to enhance the economic value of animal waste while fostering a healthier community environment. The research utilized a participatory approach, involving observation, socialization, and implementation phases. Initially, field observations and interviews with local farmers were conducted to assess potential resources and challenges. Following this, community engagement sessions were held to identify specific problems and co-develop solutions aligned with local needs. The materials for the fertilizer included cow and goat manure, chicken manure, rice husk charcoal, bran, humic acid, bio activators, molasses, and Trichoderma. The participatory action research method facilitated direct practice and continuous monitoring of organic fertilizer production. Data analysis involved qualitative techniques, focusing on community feedback and economic impact assessment. Results indicated a significant shift in community mindset towards adopting organic fertilizers, with an economic benefit increase by 30% for the participating farmers. The project successfully demonstrated that organic fertilizer could replace chemical alternatives, promoting sustainable agriculture and improving the economic landscape of Desa Mrican. In conclusion, this initiative not only provided an innovative solution to waste management but also contributed to the socio-economic development of rural communities. The study highlights the importance of community involvement and education in driving environmental sustainability. Future research should explore scaling such initiatives to broader regions to maximize environmental and economic benefits. KEYWORDS Sustainable Agriculture, Animal Waste, Eco-Friendly Fertilizer, Community Engagement, Economic Impact